Incidence and recovery of smell and taste dysfunction in COVID-19 positive patients - Al-Zaidi, Haider Majid Haider (Egypt J Otolaryngol, 2020)
BACKGROUND: This study aims to find the chemosensitive dysfunction incidence in COVID-19-positive patients and its recovery. We collected the data from sixty-five patients, all COVID-19 positive, quarantined in-hospital between 5 April 2020 and 17 May 2020, by a questionnaire distributed in the quarantine ward. RESULTS: Smell dysfunction appeared in 89.23% with or without other symptoms of COVID-19. 39.66% of them recovered the sense of smell. Taste dysfunction found in 83.08% patients with other COVID-19 symptoms. Only 29.63% of them recovered. The recovery took 1–3 weeks, and most cases recovered within 1 week or less. 18.46% and 15.38% had smell and taste dysfunction, respectively, as the only symptom before COVID-19 confirmation. Most of the chemosensitive dysfunction affected the 4th decade of age in this study. CONCLUSION: Chemosensitive dysfunction is associated with coronavirus disease and may be the only symptom that presents the disease. This makes the ENT doctors the first line of contact with the coronavirus. Further objective studies are required to cover chemosensitive dysfunctions, as the recognition of this dysfunction may help the diagnosis of COVID-19, and prevent the spread of this disease.